2002
DOI: 10.1002/1521-3773(20020802)41:15<2840::aid-anie2840>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Incorporation of Alkenes into Proteins in Escherichia coli

Abstract: Synthetic anchor: An incorporated allyl group may act in this way to allow protein modification in a site‐specific fashion. The nonnatural amino acid O‐allyl‐L‐tyrosine (1) has been site‐specifically incorporated into protein in E. coli. The yield of full‐length mutant Z‐domain protein is 5.6 mg L−1, in comparison to 9.2 mg L−1 of native Z‐domain protein. A high‐resolution mass spectrum suggests the fidelity for the incorporation of 1 is better than 99.8 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 21 publications
0
40
0
3
Order By: Relevance
“…To date, Ͼ25 unnatural amino acids have been incorporated into proteins in response to the amber nonsense codon, TAG, with high translational efficiency and fidelity. These include amino acids that can be photocrosslinked, glycosylated amino acids, chemically reactive amino acids (containing keto, alkene, or alkyne groups), redox active amino acids and fluorescent amino acids (2,3,5,(7)(8)(9). To genetically encode 22 or more amino acids requires additional codons that uniquely specify each new amino acid.…”
mentioning
confidence: 99%
“…To date, Ͼ25 unnatural amino acids have been incorporated into proteins in response to the amber nonsense codon, TAG, with high translational efficiency and fidelity. These include amino acids that can be photocrosslinked, glycosylated amino acids, chemically reactive amino acids (containing keto, alkene, or alkyne groups), redox active amino acids and fluorescent amino acids (2,3,5,(7)(8)(9). To genetically encode 22 or more amino acids requires additional codons that uniquely specify each new amino acid.…”
mentioning
confidence: 99%
“…In this approach, an orthogonal transfer RNA (tRNA)-aminoacyl tRNA synthetase pair is evolved that uniquely recognizes the amino acid of interest and selectively incorporates it into proteins in response to the amber nonsense codon, TAG. This methodology has been used to site-specifically incorporate a variety of unnatural amino acids into proteins with high fidelity and good efficiency, including amino acids with novel functional groups (3)(4)(5)(6), photocrosslinkers (7,8), heavy atoms, sugars (9), and redox active moieties. In addition, new orthogonal tRNA-synthetase pairs have been evolved from leucyl (10), lysyl, glutaminyl (11), aspartyl (12), and tyrosyl (13) tRNA-synthetase pairs to expand the number and structural diversity of amino acids that can be genetically encoded in bacteria and yeast.…”
mentioning
confidence: 99%
“…2 (6-8)) [33, [62][63][64]. Alkenes can undergo olefin metathesis reactions with another alkene molecule [64,65], or Mizoroki-Heck reactions with unsaturated halides [66,67].…”
Section: Bioorthogonal Labeling Of Proteinsmentioning
confidence: 99%
“…Both need appropriate organometallic catalysts, however. Recent research has reported water-soluble catalysts, but their applications to diverse proteins and in living cells remain to be established [60][61][62][63]. In addition, Lin and coworkers reported a UV light-induced coupling reaction between olefins and tetrazoles (Fig.…”
Section: Bioorthogonal Labeling Of Proteinsmentioning
confidence: 99%